Monetary Carbon Values in Policy Appraisal An Overview of Current Practice and Key Issues - Smith, Stephen (OECD Environment Working Papers, 2015)
Cost-benefit analyses and other quantitative appraisals are used in many countries to support decision-making in different areas of public policy, including many investment projects in sectors such as transport and energy. These decisions can have significant effects - either negative or positive - on future emissions of carbon dioxide and other greenhouse gases and it is important whether, and how, countries incorporate estimates of the marginal value of changes in carbon dioxide emissions into these analyses. This paper discusses the range of approaches which can be employed to value changes in carbon emissions in policy appraisals, setting out the key issues in the choice of valuation principles, and presents some case studies and a survey of current practice in OECD countries